The reverse racism effect: are cops more hesitant to shoot black than white suspects? - James, Lois (Criminology & public policy, 2016)
Race‐related debates often assume that implicit racial bias will result in racially biased decisions to shoot. Previous research has examined racial bias in police decisions by pressing “shoot” or “don't‐shoot” buttons in response to pictures of armed and unarmed suspects. As a result of its lack of external validity, however, this methodology provides limited insight into officer behavior in the field. In response, we conducted the first series of experimental research studies that tested police officers and civilians in strikingly realistic deadly force simulators.